Caracterização morfológica do peixe cachimbo Microphis lineatus (Kaup, 1856) na costa brasileira (Teleostei, Syngnathiformes, Syngnathidae) - Corazza, Beatriz Martins (Universidade Federal de São Carlos, 2021)
Syngnathidae includes seahorses, sea dragons and pipefishes, such as the species Microphis lineatus, which occurs in fresh, estuarine and marine waters off the Atlantic coast, from the USA to Brazil, and Pacific coast of Panama in the canal zone. It presents taxonomic uncertainty and is recognized as a species by some researchers and subspecies by others. Forty years ago, a clinal variation of three meristic data on the Brazilian coast was observed, with counts increasing in the north-south direction. The relatively small amount of material available at the time, however, hindered a better understanding of these clines. This study aimed to morphologically characterize M. lineatus in the Brazilian coast, making it possible to explore such clines with material accumulated in this period, in addition to providing subsidies for a future taxonomic review of the species. Seventeen morphometric and twelve meristic characters were taken from 209 specimens from six Brazilian ichthyological collections. The three characteristics with putative clines were corroborated (number of dorsal-fin rays, total number of subdorsal rings and number of tail rings). The symmetry analysis of the pectoral fins with the counting of their rays showed the absence of bilateral asymmetry in this characteristic. A new southern limit for the distribution of M. lineatus is proposed here: Rio Grande do Sul.
Morphological characterization of the pipefish Microphis lineatus (Kaup, 1856) along the Brazilian coast (Syngnathiformes: Syngnathidae)
Keywords: caracteres merísticos; variação clinal; morfometria; meristic characters; morphometry; clinal variation; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES